Does Degree of Stringency Matter? Revisiting the Pollution Haven Hypothesis in BRICS Countries - Wen, Yuzhao; Haseeb, Mohammad; Safdar, Noreen; Yasmin, Fouzia; Timsal, Sajida; Li, Zaijun (Frontiers in Environmental Science, 2022)
The focus of this study is to demonstrate the validity of Pollution Haven Hypothesis (PHH) for BRICS nations by revealing the empirical relationship between foreign direct investment (FDI), air pollution, and environmental regulations. The panel data is utilized for the years 2000 to 2020. Environmental regulations are the primary determinant of foreign direct investment; the severity of ecological regulations is graded on a scale from 1 to 7, where 7 represents "very stringent" regulations and 1 represents "very lax" regulations. The study emphasizes estimation as the most significant technique the PMG/PARDL, therefore, the empirical estimates indicate that increase in FDI also increases environmental degradation; thus, the findings confirm the existence of PHH in BRICS. The results show that these low stringency index values increase CO2 emissions by attracting pollution intensive FDI. When the stringency value is low, pollution rises; if this index is increased, pollution can be controlled due to a greener and cleaner FDI attraction. If environmental regulations are lax or nonexistent, the results demonstrate that pollution havens may exist.